The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1149/1.2166510
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Physical-Chemical Vapor Deposition of Ti-Si-N-O Barrier Films

Abstract: Ti-Si-N-O films were grown by radio frequency reactive magnetron sputtering of a titanium target with nitrogen and silane gases introduced at a temperature of 40°C. X-ray diffraction and X-ray photoelectron spectroscopy results show that Ti-N, Si-N, Ti-Si, Ti-O, Si-O, and Si-N-O compounds are formed. High-resolution-transmission-electron-microscopy reveals that the film consists of Ti-N, Si-N, Ti-Si nanocrystals embedded in an amorphous Ti-O, Si-O, and Si-N-O matrix. This type of microstructure gives rise to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…Silicon levels between 12 and 15 atom % was obtained by varying the silane gas ͑SiH 4 ͒ flow rate from 20 to 40 sccm while nitrogen and argon gas flow rate were maintained at 30 and 20 sccm, respectively. The Si/Ti atomic ratio as a function of silane gas flow rate is reported in Table I 29 The barrier performance of these three different compositions of Ti-Si-N-O vs the metal ion diffusion was evaluated through BTS testing.…”
Section: Resultsmentioning
confidence: 99%
“…Silicon levels between 12 and 15 atom % was obtained by varying the silane gas ͑SiH 4 ͒ flow rate from 20 to 40 sccm while nitrogen and argon gas flow rate were maintained at 30 and 20 sccm, respectively. The Si/Ti atomic ratio as a function of silane gas flow rate is reported in Table I 29 The barrier performance of these three different compositions of Ti-Si-N-O vs the metal ion diffusion was evaluated through BTS testing.…”
Section: Resultsmentioning
confidence: 99%
“…Recientemente se han fabricado películas de TiSiNO para que actúen como barreras contra la difusión (Ee et al, 2006b(Ee et al, , 2006c(Ee et al, , 2006dShalaeva et al, 1999), debido a sus prometedoras propiedades, que los hacen fuertes candidatos para la siguiente generación de barreras de difusión en la tecnología CMOS. Estudios realizados sobre este sistema cuaternario, revelan que estos recubrimientos están formados de nanocristales embebidos generalmente en fases amorfas de Ti-O, Si-O, Si-N y Si-N-O (Shalaeva et al, 1999).…”
Section: Introductionunclassified
“…Shalaeva desarrollo un estudio muy completo acerca de la composición de fases (diagrama metaestable) de estas películas de Ti-Si-N-O (Shalaeva et al, 1999), el cual es formado a partir del diagrama de equilibrio de los sistemas Ti-Si-N y Ti-Si-O. Otros autores se han enfocado a estudiar la resistividad de dicho sistema cuaternario en función del efecto que producen los parámetros de fabricación sobre su microestructura, morfología superficial, rugosidad y tipos de enlace químico (Ee et al, 2006b(Ee et al, , 2006c(Ee et al, , 2006d. Sin embargo, un estudio referente a su dureza, aun no ha sido reportado y mucho menos comparado con su resistividad.…”
Section: Introductionunclassified
“…Also, Ti-Si-N-O coatings have been fabricated to act as a diffusion barrier ( Ref 11,12) due to their promising properties, which make them strong candidates for the next generation of diffusion barriers in CMOS technology. Smith and Custer (Ref 13), found that resistivity varies from 400 lX cm for TiN to 1 · 10 6 lX cm for Ti-Si-N. Ee et al (Ref 14) obtained resistivity values from 3.63 · 10 3 lX cm to up to 6.45 · 10 6 lX cm for the system Ti-Si-N-O fabricated by rf reactive magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%